Safety and Immunogenicity of Co-Administration of Herpes Zoster Vaccines with Other Vaccines in Adults: A Systematic Review and Meta-Analysis - Omid Rezahosseini; Aysan Bazargan; Mads Frederik Eiberg; Alexander Printzlau Korsgaard; Raziyeh Niyati; Christina Ekenberg; Lars Nørregaard Nielsen; Zitta Barrella Harboe (Vaccines)
Introduction: Herpes zoster (HZ), or shingles, is a vaccine-preventable disease with two approved vaccines: the live-attenuated vaccine (LZV) and the adjuvanted recombinant zoster vaccine (RZV). Evidence on the immunogenicity and adverse events (AEs) following co-administration with other vaccines in adults is limited. This systematic review and meta-analysis aims to evaluate the immunogenicity and safety of HZ vaccines when co-administered with other vaccines. Methods: We followed PRISMA 2020 guidelines and systematically searched multiple databases (January 1950 to February 2024) for studies on HZ vaccination with concomitant vaccines in adults (≥18 years). Observational studies, randomized controlled trials (RCTs), and non-randomized controlled trials were included, excluding reviews, case series, case reports, editorials, and non-English publications. Risk of bias was assessed using Cochrane tools (RoB 2 and ROBINS-I). A meta-analysis compared geometric mean concentration (GMC) ratios and vaccine response rates (VRRs) for RZV, applying the Hartung–Knapp adjustment. For LZV, meta-analysis was not feasible, and results were described narratively. AEs were analyzed using risk ratios and presented in forest plots. Results: Out of 369 search hits, ten RCTs were included. In six RCTs, RZV was co-administered with influenza, COVID-19, pneumococcal vaccines (PCV13, PPSV23), or Tdap. The pooled GMC mean difference was −0.04 (95% CI: −0.10 to 0.02, p = 0.19), and the pooled VRR was 1.00 (95% CI: 0.99 to 1.01, p = 0.59). Local and systemic AEs showed pooled relative risks of 0.99 (95% CI: 0.95 to 1.03, p = 0.73) and 1.01 (95% CI: 0.91 to 1.11, p = 0.90), respectively. LZV co-administration was investigated in four RCTs and was safe; however, co-administration with PPSV23 resulted in reduced immunogenicity. Conclusions: The co-administration of RZV with other vaccines was safe and immunogenic. However, limited evidence suggests that co-administration of LZV with PPSV23 reduced the immunogenicity of LZV through an unknown mechanism. Still, RZV co-administration could enhance vaccine uptake in vulnerable populations.